Strategic Repositioning of the Islamic Education Management Study Program at PTKI: Integration of Results-Based Quality Management to Enhance Graduate Competitiveness - Abidin Nasyar; Devi Fatwanti; Encep Syarifudin; Eneng Muslihah; Siti Patimah (CV. Edujavare Publishing, 2026)
This study examines efforts to reposition the Islamic Education Management (MPI) Study Program within the Islamic Religious Higher Education (PTKI) ecosystem through a strategic review of national regulations and curriculum adaptability to workplace demands. This research aims to formulate strategic steps to align the curriculum and quality management practices with industry needs to improve graduate competitiveness. Although the MPI curriculum development has referred to the Indonesian National Qualifications Framework (KKNI) and Graduate Learning Outcomes (CPL), tracer study data still shows low absorption of graduates into managerial positions and relevant educational fields. Meanwhile, DIKTIS policies, such as the PTKI Curriculum Guide and KMA No. 347/2022, have established quality standards, but their implementation remains hampered by structural and cultural barriers at the study program level. Using literature study methods and institutional policy analysis through official documents and empirical data from several PTKIN, this study finds an urgent need for a paradigm shift from administrative management to outcome-based quality management supported by cross-sector collaboration. The repositioning of MPI demands the presence of an adaptive curriculum, strategic partnerships with the industrial world, and the active role of DIKTIS as a solution-oriented policy facilitator.